2012
DOI: 10.3109/13685538.2012.669436
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress increases continuously with BMI and age with unfavourable profiles in males

Abstract: Oxidative stress is a risk factor for chronic diseases and was previously shown to be independently associated with obesity. The authors investigated the relationship between body mass index (BMI), age and oxidative stress on 2190 subjects undergoing a health care examination. Total antioxidant status (TAS), total peroxides (TOC) and autoantibodies against oxidized LDL (oLAb) were used as oxidative stress biomarkers in addition to serum lipoproteins, bilirubin and uric acid. Gender-specific differences were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
46
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 42 publications
11
46
1
2
Order By: Relevance
“…A speculative explanation to this observation is bilirubin consumption occurring in obesity, a hypothesis shared by others (24); obesity is associated with increased inflammation [16], [37], [38] and oxidative stress [39], [40], and bilirubin, presenting antioxidant and anti-inflammatory properties [9], [10], may be somewhat consumed. In fact, oxidative stress increases with increasing BMI and age [34]. In line with this, we found that bilirubin levels are negatively correlated with body and trunk fat percentages and CRP levels within obese patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A speculative explanation to this observation is bilirubin consumption occurring in obesity, a hypothesis shared by others (24); obesity is associated with increased inflammation [16], [37], [38] and oxidative stress [39], [40], and bilirubin, presenting antioxidant and anti-inflammatory properties [9], [10], may be somewhat consumed. In fact, oxidative stress increases with increasing BMI and age [34]. In line with this, we found that bilirubin levels are negatively correlated with body and trunk fat percentages and CRP levels within obese patients.…”
Section: Discussionsupporting
confidence: 87%
“…Total and direct bilirubin levels were reported to be higher in normal weight adult males than in females [24], [34], [35], but similar within overweight patients [24]. In our study, we observed no statistical significant differences between boys and girls regarding TB levels, either in controls or in obese patients.…”
Section: Discussioncontrasting
confidence: 51%
“…Nevertheless, there is a possibility that the observed pathway enrichments for genetic association can be attributed to BMI, which is in the causal pathway, because an increase in BMI elevates oxidative stress in the body (Wonisch et al , 2012). In post-hoc regression analyses of BMI, we observed that the low-frequency variants were not associated with BMI (Table S2, online supporting information).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent research publication, Wonisch et al reported that oxidative stress (more pro-oxidants) increased with age and BMI in a population of 2,190 male subjects undergoing a health examination. 37 Recently, Bryan et al published a review article that explore the role of reactive oxygen species (ROS) in constructive inflammation and wound healing. 38 Leukocytes, utilizing ROS, clean compromised tissue and eliminate pathogenic organisms; however, a long-term imbalance of pro-oxidants may compromise the wound healing rate and efficiency of new tissue deposition.…”
mentioning
confidence: 99%